RealTime Pendaftaran Pasien Berbasis Web Service dan SMS Gateway : Pada Masa PSBB di Klinik Karisma Medika - Cynthia Hayat (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Abstract— The current COVID-19 pandemic has an impact on all sectors of life where the government has set a policy of Large-Scale Social Restrictions (PSBB). The existence of restrictions on activities known as 3M requires Karisma Medika Clinic to adapt its operational workflow by utilizing information technology to adapt patient registration. To make it easier for patients to register and get a queue number by developing a web service-based application and SMS Gateway. The application is developed based on a web service using the Codeigniter framework with a flow of information procedures regarding the attending physician, then after selecting a doctor, will go to the registration section to fill in personal data and symptoms and complaints for consultation. The data entered in the application will be stored in the Gammu SMS engine database and through the SMS gateway, patients will receive a queue number for consultation at the clinic in real time which will continue to be updated. User response tests from 25 respondents showed that it was easy for patients to register by paying attention to health protocols of 92.25% (very easy), 5% (easy), and 2.75 % quite easy. While the satisfaction indicator is 95% (very satisfied) and 5% of respondents (satisfied).